Predicting of financial distress using logistic regression approach / Noryana Abd Latip - Abd Latip, Noryana (2007)
This project paper is done in order to determine the financial ratio that can be used as a predictor of financial distress for firms listed under Syariah Stock. In order to find and prove that the selected firms are in financial distress, the analysis and review of financial position of the firms has been done. In this project paper, populations are selected from Main board which have 126 companies and second board have 115 companies. The sample only consist 28 companies in Main board and 6 companies in Second board. This project paper used the income statement and balance sheet for the three years from 1998 to 2001 in order to select which the companies as a distress or health company. From the sample we used the data from 1993 to 1996 to predict the financial distress. The data collected will be conducted and analyze using Logistic Regression Approach. The financial distress has significant relationship with activity ratio. Observation and recommendations are presented at the end of the project to be used to all people who interested in this area